At the intersection of materials, engineering, and new business creation. (December 2015) - Galvin, Gregory J.; Zhou, Peng; Davis, Timothy J.; Desai, Shahyaan; Collins, Shane
Abstract: Abstract : Engineering, whether in the form of product development or manufacturing processes, often drives the selection or creation of new materials in order to meet performance requirements. Conversely, development of new materials, or new ways to process materials, can lead to new engineering capabilities that, in turn, lead to new products or improved product performance. The interplay between materials and engineering is dynamic, ongoing, and critical to the success of many new products and industries. In this article, we take examples of this interplay from four technology companies in different industries developing widely different materials systems. Each example demonstrates the critical role that materials play in creating new products, new manufacturing methods, and even new design methodologies. Our examples come from polymer microfluidic devices, silicon- and nonsilicon-based microelectromechanical systems, and metals additive manufacturing.